Studies on the processing of plasma and patient samples - Hemmilä, Emilia (My University, 2024)
Radiometer Turku Oy manufactures semi-products used for quality control purposes for the AQT90 Flex products. These semi-products consist of a plasma matrix and either endogenous antigen from a patient sample pool or recombinant antigen. Plasma matrices and patient sample pools are filtered before use to prevent the blockage of the AQT90 Flex sample needle. This process is challenging due to filtration rigidness and slow sample flow through, resulting in sample loss and higher manufacturing costs. Therefore, the aim of this study was to investigate the patient sample pool filtration to remove clots without significant sample loss. Plasma, used as a matrix, is processed for seven days before use, and this long protocol is inconvenient for Production. In addition, at least one alternative vendor is needed for the plasma matrix to secure material availability. The other aims of the study were to test shorter plasma thawing protocols and to test plasma from an alternative vendor as a semi-product plasma matrix. In this study, filters from different manufacturers were tested for patient sample pool filtration. In addition, the necessity of patient sample pool filtration was studied by comparing plasma matrices spiked with either centrifuged or centrifuged and filtered patient sample pools. In terms of plasma processing, plasma thawing at +4 °C for 24 hours or at +37 °C for an hour was tested, and the results were compared to the current plasma thawing protocol. Additionally, the stabilities of two antigens were tested in three different plasma lots from an alternative plasma vendor. In filter testing, it was discovered that a larger disc filter diameter and effective filtration area allow better sample flow-through. In addition, the Saint-Gobain disc filters, and the PALL Macrosep Advance centrifugal device showed promise as potential filter options for patient sample pool filtration due to their efficacy and ease of use. Furthermore, in the patient sample pool filtration experiment, a ≥9 % patient sample pool volume ratio to total plasma volume resulted in the clotting of the plasma matrix despite the filtration of the patient sample pool. In the plasma thawing experiment, processed plasma thawed at +4 °C for 24 hours did not clot during storage at +4 °C, whereas processed plasma thawed at +37 °C did. Additionally, antigens under investigation preserved their stability in plasma thawed at +4 °C for 24 hours or at +37 °C for an hour. In alternative plasma vendor testing, both used antigens were stable in all three plasma lots. This study provided further information on plasma and patient sample pool processing. However, further testing is still needed on the patient sample pool filtration, the introduction of a new plasma thawing protocol, or an alternative plasma vendor to the manufacturing process.
Keywords: AQT90 Flex, patient sample pool filtration, plasma coagulation, plasma thawing